Optimum length for pin fins used in electronic cooling - Mafeed, M. P.; M., Salman Ali; C., Prabin; Ramis, M. K.; Ali Baig, M. A.; Khan, Sher Afghan (Trans Tech Publications Ltd., Switzerland, 2012)
The present work deals with the heat transfer analysis of pin fins of various geometries namely ─ circular, triangular and rectangular and thus arrive at the optimum design. To this end, the fin with convective boundary tip is considered and the equation governing the one-dimensional heat conduction in the fin is solved analytically to obtain the temperature distribution and heat transfer rate. A computer code has been developed to generate results for wide range of parameters─ heat transfer coefficient h, thermal conductivity k, and length of the fin l. Results are plotted in the form of temperature variation, heat transfer variation and optimum length variation. From the detailed discussion of the results it can be concluded optimum length decreases with increasing heat transfer coefficient and it increases with increasing thermal conductivity. It can be also concluded that the optimum length is minimum for a triangular fin compared to rectangular and circular fins.